Fundamental British Values: Radicalizing British Children Into a Manufactured Them and Us Narrative Concept of Britishness?. Issue 1 (May 2020) - Hodkinson, Alan
In 2014, the United Kingdom Coalition Government, after the now infamous Trojan Horse incident, insisted that all children learn Fundamental British Values. Cameron, as Prime Minister, argued that such values, coupled with "muscular liberalism" would "challenge extremist ideology, exposing it for the lie that it is." This article exists at the place of the apostrophe—as the scare mark (' ') becomes an enclosure, enclosing a manufactured possession. "Is Britishness just a made up concept? Who determines what is or is not fundamental?: I want to problematize what they include and exclude in their concept of "British Values." What is this "British" they talk about and why do they feel a need for this "Britain" to exist? Within the enclosures provided by 'ten scare marks', I present research into historical and contemporary formulations of Britishness taken from academic texts, school textbooks, and websites. In addition, by invoking the work of Serres, Bhabba, and Billig, I seek to confront Cameron's challenging discourse. Within this article, I do not though attempt to detail an authentic Britishness but rather from the outset argue that there is, and This analysis is disturbing. It disturbs my thoughts but also my personal history- it is troubling: never was any authenticity in this concept. What I seek to argue here is that their "British-ness" is nothing more than a portable, lean-to concept of violence. A "manufactured concept" (Nationalism and the origins of prejudice, International Journal of Historical Teaching, Learning and Research ) which locates an inclusion but by default formulates an exclusion whose antecedents lie more in the government counter terrorists' strategies than any substantial historical fact If it is manufactured where does this leave my schooling – which told me Britain was great?: (Britishness from a linguistic perspective in school textbooks). The paper concludes by suggesting that their "Britain" is a rhetorical trope. It is itself a Trojan horse—which through flagging and banal nationalism (Banal nationalism) indoctrinates and radicalizes our children into an invented—pererted nationalism that the political elite employs to deal with a perceived/conceived/contrived threat of an internal other to our geographical, historical, and ideological borders.